2019
DOI: 10.3390/su11184946
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency and Economic Viability as Decision Factors in the Rehabilitation of Historic Buildings

Abstract: The restoration of historical buildings often implies a change in the main use of the building so that it can once again become a part of people’s lives. Among the interventions needed to adapt the buildings to their new purpose, improving the energy performance is always a challenge due to their particular construction solutions and the influence that these improvements can have on their protected elements. The regulations in force in European Union (EU) member states leave a gap in how the energy performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In specific for built heritage, behaviour is frequently mentioned as a synonym of "performance", referring to physical characteristics of the building. While in the construction sector, in general, there is raising awareness of the role of occupants' behaviour for sustainability and energy efficiency (Caro & Sendra, 2020;Chen, Ding, Bai, & Sun, 2020;Gianfrate, Piccardo, Longo, & Giachetta, 2017;Laaroussi, Bahrar, El Mankibi, Draoui, & Si-Larbi, 2020), in the specific field of built heritage, occupants' behaviour is only mentioned as a factor that affects performance, without a more in-depth analysis of the underlying socio-psychological factors (Ajzen, 1985;Berg & Donarelli, 2019;Galiano-Garrigós, González-Avilés, Rizo-Maestre, & Andújar-Montoya, 2019;Mutani, Todeschi, Kämpf, Coors, & Fitzky, 2018). A systematic literature review on behaviour and heritage conservation found no results targeting practitioners' behaviour towards the implementation of sustainable conservation practices (Gonçalves et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In specific for built heritage, behaviour is frequently mentioned as a synonym of "performance", referring to physical characteristics of the building. While in the construction sector, in general, there is raising awareness of the role of occupants' behaviour for sustainability and energy efficiency (Caro & Sendra, 2020;Chen, Ding, Bai, & Sun, 2020;Gianfrate, Piccardo, Longo, & Giachetta, 2017;Laaroussi, Bahrar, El Mankibi, Draoui, & Si-Larbi, 2020), in the specific field of built heritage, occupants' behaviour is only mentioned as a factor that affects performance, without a more in-depth analysis of the underlying socio-psychological factors (Ajzen, 1985;Berg & Donarelli, 2019;Galiano-Garrigós, González-Avilés, Rizo-Maestre, & Andújar-Montoya, 2019;Mutani, Todeschi, Kämpf, Coors, & Fitzky, 2018). A systematic literature review on behaviour and heritage conservation found no results targeting practitioners' behaviour towards the implementation of sustainable conservation practices (Gonçalves et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variety of stakeholders involved in the complex processes of building conservation, no significant number of studies were found analysing their behaviours leading to the implementation (or not) of planned intentions. Occupants' behaviour is an exception in the building and construction sector and it is often referred to by its impact on the energy performance of buildings [217][218][219][220][221][222]. However, the literature review points occupant behaviour as a factor-one of several things that influence the results, but not as the core of the detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-relatedness of economic viability and efficiency is long recognized in economics literature [26]. There is a renewed interest in the joint-estimation of economic viability and efficiency in sustainability studies on various fields including energy [42], and agriculture [43,44]. Therefore, the best model should be the one that considers the metafrontier efficiency as a latent variable to reproductive threshold representing economic viability.…”
Section: Regression Analysis: Structural Equation (Sem) Modelmentioning
confidence: 99%